2014
DOI: 10.1002/ca.22482
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the internal iliac veins in the presacral area: Clinical implications during sacral colpopepxy or extended pelvic lymphadenectomy

Abstract: The purpose of this study was to classify anatomical variations of the internal iliac vein (IIV) in relation to robotic or laparoscopic extended lymphadenectomy. Between March 2011 and July 2012, 60 consecutive patients underwent robotic or laparoscopic extended lymphadenectomy. We retrospectively reviewed surgical video clips and analyzed the pattern of the IIVs in the presacral area. IIV variations were classified into seven types: Type A, normal (n = 39, 65.0%); Type A with a dilated middle sacral vein (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…That is why a profound knowledge of the distribution and constitution of the IIV is, in the majority of cases, bleed sparing. This is true for the scheduled as well as for the urgent surgical scenario [6][7][8] .…”
Section: Discussionmentioning
confidence: 96%
“…That is why a profound knowledge of the distribution and constitution of the IIV is, in the majority of cases, bleed sparing. This is true for the scheduled as well as for the urgent surgical scenario [6][7][8] .…”
Section: Discussionmentioning
confidence: 96%
“…In addition, when performing LLND, after performing one side, the branch patterns of the IIV on the opposite side can be predicted. Certainly, some studies demonstrated the complex anatomy of IIVs and their branches [16][17][18][19][20]. However, the patterns of the IIV can basically be divided into two patterns: Adachi's classification Types I and IV.…”
Section: Discussionmentioning
confidence: 99%
“…To solve those problems, several studies have attempted to investigate the branch patterns of the IIVs. However, these studies focused on common internal and external iliac veins, and the peripheral sides of the veins were not well investigated [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The right ureter should be seen throughout the entire dissection process in order to avoid damages to the right iliac vessels and ureter. The vascular anatomy is extremely variable [8]. To date, the literature has strongly emphasized these variants which must be known to avoid bleeding complications, while the bone component and the study of the bone promontory were less explored.…”
Section: Discussionmentioning
confidence: 99%